2010
DOI: 10.3945/jn.110.121202
|View full text |Cite
|
Sign up to set email alerts
|

Oral Nutritional Supplements Containing (n-3) Polyunsaturated Fatty Acids Affect the Nutritional Status of Patients with Stage III Non-Small Cell Lung Cancer during Multimodality Treatment

Abstract: Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), (n-3) fatty acids from fish oil, have immune-modulating effects and may improve nutritional status in cancer. The objective of this study was to investigate the effects of an oral nutritional supplement containing (n-3) fatty acids on nutritional status and inflammatory markers in patients with non-small cell lung cancer (NSCLC) undergoing multimodality treatment. In a double-blind experiment, 40 patients with stage III NSCLC were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
136
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(148 citation statements)
references
References 57 publications
6
136
1
5
Order By: Relevance
“…An interesting next step will be to investigate whether interventions, such as nutritional and exercise interventions, which have the potential to counteract the SMM loss during intensive treatment and support potential gain during less intensive treatment, also result in improved outcome of treatment. A gain in SMM has recently be shown in nutritional intervention studies in which protein and/or omega 3 fatty acids enriched high energy were added to the diet of non‐small cell lung carcinoma patients,26, 27, 28 and in an exercise intervention study performed during chemotherapy for breast cancer, a significant increase of muscle strength was observed in the intervention group 29. Especially, a multimodal approach in which nutrition and exercise are combined might provide a promising future strategy to prevent SMM loss and subsequent reduced treatment outcomes 30…”
Section: Discussionmentioning
confidence: 99%
“…An interesting next step will be to investigate whether interventions, such as nutritional and exercise interventions, which have the potential to counteract the SMM loss during intensive treatment and support potential gain during less intensive treatment, also result in improved outcome of treatment. A gain in SMM has recently be shown in nutritional intervention studies in which protein and/or omega 3 fatty acids enriched high energy were added to the diet of non‐small cell lung carcinoma patients,26, 27, 28 and in an exercise intervention study performed during chemotherapy for breast cancer, a significant increase of muscle strength was observed in the intervention group 29. Especially, a multimodal approach in which nutrition and exercise are combined might provide a promising future strategy to prevent SMM loss and subsequent reduced treatment outcomes 30…”
Section: Discussionmentioning
confidence: 99%
“…There has been only one previous randomised omega-3 PUFA intervention trial in cancer patients that has reported individual omega-3 PUFA levels during treatment [6] and none that have included an analysis of omega-3 PUFA 'washout' after cessation of omega-3 PUFA supplementation. Van der Meij et al described variability in plasma phospholipid EPA levels after double-blind intervention for 5 weeks with a daily supplement containing 2 g EPA and 0.9 g DHA or isocaloric control in patients with non-small cell lung cancer [6].…”
Section: Discussionmentioning
confidence: 99%
“…Van der Meij et al described variability in plasma phospholipid EPA levels after double-blind intervention for 5 weeks with a daily supplement containing 2 g EPA and 0.9 g DHA or isocaloric control in patients with non-small cell lung cancer [6]. These authors obtained similar individual EPA profiles to the EMT study with a number of 'non-responders' in the intervention arm and, conversely, some individuals with high baseline EPA values or an 'EPA response' in the control arm of the study [6]. We suggest that contamination is likely to occur in all trials of omega-3 PUFA supplements with individual randomisation and can be, at least partly, adjusted for by analysis by absolute or relative change in RBC omega-3 PUFA levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RBC fatty acid analysis not only demonstrates the systemic increase in o3, but is also a stable measure of intake, with low biological variability and measures long-term intake. 32 Other objective methods include measuring o3 PUFAs in swabs of buccal cells, 33 plasma phospholipid fatty acid concentrations, 33,34 and EPA + DHA proportions in plasma cholesterol esters. 30 Although, analyzing buccal cells is less invasive than blood tests, the amount of total lipid on the swabs was very small, and the measurement of o3 PUFAs was highly variable and unreliable.…”
Section: Figmentioning
confidence: 99%